Live Successfully, Don't Be Afraid: Internal Locus Of Control And Fear Of Success In Career Women - Walewangko, Alexandra Celadine Katya; Wibowo, Doddy Hendro (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
Every woman has equal opportunities, rights and freedoms with men to develop her career. There is a view that if women can achieve success, they will get negatif consequences from their social environment. The purpose of this study was to find out whether there is a relationship between Internal Locus Of Control and Fear Of Success in career women. This study uses a correlational quantitative method. By determining the sample using non-probability sampling technique, namely accidental sampling. The participants involved in this study were 101 career women. The scale trial produced a reliability coefficient on the Internal Locus Of Control scale of 0.796 and on the Fear Of Success scale of 0.909. The data analysis technique used is product moment analysis by obtaining a correlation coefficient of r = -0.658 and a significance value of 0.000 (p <0.05) meaning that this indicates that there is a negatif relationship between Internal Locus Of Control and Fear Of Success in career woman.Setiap wanita mempunyai kesempatan, hak serta kebebasan yang setara dengan kaum pria untuk mengembangkan kariernya. Terdapat pandangan apabila wanita dapat mencapai sebuah kesuksesan maka akan mendapatkan dampak negatif dari lingkungan sosialnya. Tujuan penelitian ini untuk mengetahui apakah terdapat hubungan antara Internal Locus Of Control dengan Fear Of Success pada wanita karier. Penelitian ini menggunakan metode kuantitatif korelasional. Dengan penentuan sampel menggunakan teknik non probability sampling, yaitu accidental sampling. Partisipan yang terlibat dalam penelitian ini sebanyak 101 wanita karier. Uji coba skala menghasilkan koefisien reliabilitas pada skala Internal Locus Of Control sebesar 0,796 dan pada skala Fear Of Success sebesar 0,909. Teknik analisis data yang digunakan adalah analisis product moment dengan memperoleh koefisien korelasi sebesar r = - 0, 658 dan nilai signifikansi sebesar 0,000 (p < 0,05) artinya hal ini menunjukkan bahwa adanya hubungan negatif antara Internal Locus Of Control dengan Fear Of Success pada wanita karier.